KUAT LEKAT TULANGAN BAMBU PETUNG TAKIKAN TIPE V DENGAN JARAK TAKIKAN 2 CM DAN 3 CM - Mustamir Saifuddin; Agus Setiya Budi; Supardi Supardi (Matriks Teknik Sipil, 2014)
Study of bond stength petung bamboo reinforcement type V notch with distance of 2 cm and 3 cm in normal concrete. This study used an experimental method with a total of 15 pieces of the test specimen . Specimens used are concrete cylinders with a diameter of 15 cm and 30 cm high . As reinforcement using bamboo reinforcement petung without nodia with the notch distance of 2 cm and 3 cm . Bamboo petung bernodia with the notch distance of 2 cm and 3 cm . Each specimen 3 pieces with type V notch , the notch width 0.8 cm and 0.5 cm depth of the notch . Bamboo reinforcement dimensions length 70 cm, width 2 cm and 0.52 cm thick . As a comparison using steel reinforcement with a diameter of 0.8 cm and a length of 70 cm specimen 3 pieces . Quality concrete with f'c = 17.5 planned MPa . Adhesion test was conducted at 28 days by using a Universal Testing Machine ( UTM ) .